2020
DOI: 10.1101/2020.11.11.20229500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of social distancing and masking with risk of COVID-19

Abstract: Given the continued burden of severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) disease (COVID-19) across the U.S., there is a high unmet need for data to inform decision-making regarding social distancing and universal masking. We examined the association of community-level social distancing measures and individual masking with risk of predicted COVID-19 in a large prospective U.S. cohort study of 198,077 participants. Individuals living in communities with the greatest social distancing had a 31% … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The interaction of these effects is exemplified in a US study of participants enrolled and using a coronavirus disease 2019 (COVID‐19) smartphone application. Individuals living in communities with the greatest social distancing had a 31% lower risk of predicted COVID‐19 compared with those living in communities with poor social distancing; even among individuals living in a community with poor social distancing, self‐reported masking was associated with a 63% reduced risk of predicted COVID‐19 10 …”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The interaction of these effects is exemplified in a US study of participants enrolled and using a coronavirus disease 2019 (COVID‐19) smartphone application. Individuals living in communities with the greatest social distancing had a 31% lower risk of predicted COVID‐19 compared with those living in communities with poor social distancing; even among individuals living in a community with poor social distancing, self‐reported masking was associated with a 63% reduced risk of predicted COVID‐19 10 …”
mentioning
confidence: 94%
“…Individuals living in communities with the greatest social distancing had a 31% lower risk of predicted COVID-19 compared with those living in communities with poor social distancing; even among individuals living in a community with poor social distancing, self-reported masking was associated with a 63% reduced risk of predicted COVID-19. 10 Even so the added value of masks to social distancing remains unclear. The DANMASK study 11 wherein all participants were encouraged to socially distance in public reported only a 0.3% between-group difference over 1 month in seroconversion rates, between no mask recommendation or a recommendation to wear a mask when outside the home for more than 3 h among other people (1.8% vs 2.1% seroconversion).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inconsistent mask wearing policies and limited enforcement mechanisms have resulted in differential rates of mask uptake across the United States (2)(3)(4). Some ecological and individual studies have found associations with reported mask wearing and changes in the SARS-CoV-2 transmission rate or self-reported positivity (1,4,5). To date, the majority of these studies have only asked, general questions about whether or not a person wears a mask when outside the home with options capturing varying degrees of adherence (e.g., always, sometimes, occasionally, and never) (5).…”
mentioning
confidence: 99%
“…Some ecological and individual studies have found associations with reported mask wearing and changes in the SARS-CoV-2 transmission rate or self-reported positivity (1,4,5). To date, the majority of these studies have only asked, general questions about whether or not a person wears a mask when outside the home with options capturing varying degrees of adherence (e.g., always, sometimes, occasionally, and never) (5). A number of other studies in individuals being monitored as part of a contact tracing program have reported that not wearing a mask increases the risk of infection but it is not clear how individuals with a known positive contact may differ from the general population, particularly those without known exposure (6).…”
mentioning
confidence: 99%